2016
DOI: 10.1371/journal.pgen.1005828
|View full text |Cite
|
Sign up to set email alerts
|

Rab6 Is Required for Multiple Apical Transport Pathways but Not the Basolateral Transport Pathway in Drosophila Photoreceptors

Abstract: Polarized membrane trafficking is essential for the construction and maintenance of multiple plasma membrane domains of cells. Highly polarized Drosophila photoreceptors are an excellent model for studying polarized transport. A single cross-section of Drosophila retina contains many photoreceptors with 3 clearly differentiated plasma membrane domains: a rhabdomere, stalk, and basolateral membrane. Genome-wide high-throughput ethyl methanesulfonate screening followed by precise immunohistochemical analysis ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 61 publications
(86 reference statements)
1
58
2
Order By: Relevance
“…Additionally, there is a reduction in the number of medial- and trans- Golgi cisternae owing to a lack of cis- Golgi cisternae that can progressively maturate into medial - and trans -Golgi cisternae. These phenotypes are distinct from that observed in Rab6 mutants, where cytoplasmic condensations of medial - and trans- Golgi resident enzymes occurs, but the amount and localization of cis -Golgi proteins remains unaffected (Iwanami et al, 2016; Satoh et al, 2016). …”
Section: Resultscontrasting
confidence: 64%
See 3 more Smart Citations
“…Additionally, there is a reduction in the number of medial- and trans- Golgi cisternae owing to a lack of cis- Golgi cisternae that can progressively maturate into medial - and trans -Golgi cisternae. These phenotypes are distinct from that observed in Rab6 mutants, where cytoplasmic condensations of medial - and trans- Golgi resident enzymes occurs, but the amount and localization of cis -Golgi proteins remains unaffected (Iwanami et al, 2016; Satoh et al, 2016). …”
Section: Resultscontrasting
confidence: 64%
“…We confirmed Golgi association of Syx5 in late pupal photoreceptors by overexpressing Syx5::Myc and found that it predominantly localizes to the puncta closely associated with the trans-side of Golgi units marked by CFP::GalT (Satoh et al, 2005) (Fig. 3A), unlike Rab6 (another Golgi protein) which localizes to Golgi units and post-Golgi vesicles at the base of the rhabdomeres (Iwanami et al, 2016). Golgi units in photoreceptors are well-developed at the early pupal stages with their width reaching above 1 µm (Satoh et al, 2005).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…4F and Fig. S4), or Rab6B and Rab8A required for multiple apical transport pathways, including rhodopsin transport to the cilium in Drosophila photoreceptors (25,26) (Fig. 4 G and H).…”
Section: Smo Inhibition Results In Accumulation Of Or-positive Punctamentioning
confidence: 99%